Ag-ZnS Embedded Polymeric Receptors for the Recognition of Human Serum Albumin - Amara Nasrullah; Muhammad Zahid; Asghar Ali; Mirza Nadeem Ahmad; Adnan Mujahid; Tajamal Hussain; Usman Latif; Muhammad Imran Din; Adeel Afzal (Chemosensors, 2023)
The detection of human serum albumin (HSA) is of significant clinical importance in disease diagnoses. In this work, polymer-based synthetic receptors are designed by incorporating Ag-ZnS microspheres in molecularly imprinted poly(methacrylic acid-co-ethylene glycol dimethacrylate) (MIPs) for the gravimetric detection of HSA. Among different compositions of Ag-ZnS@MIPs, MIPs having methacrylic acid and ethylene glycol dimethacrylate volume ratio of 3:2 exhibit enhanced HSA sensitivity in the concentration range of 5–200 ng/mL. A remarkably low threshold limit of detection (LOD = 0.364 ng/mL) is achieved with quartz crystal microbalance (QCM) based gravimetric sensors. Furthermore, the Ag-ZnS@MIPs/QCM sensors show high selectivity for HSA compared to other proteins, e.g., bovine serum albumin (BSA), glycoprotein, ribonuclease, and lysozyme. Hence, the gravimetric quantification of HSA realizes a highly sensitive, selective, and label-free detection mechanism with a limit of quantification down to 1.1 ng/mL.